THE PSYCHOLOGICAL EXPRESSIVE FUNCTION OF SOUND DESIGN IN CONTEMPORARY UZBEK FEATURE FILMS (International journal of artificial intelligence, 2026)
This article examines the psychological expressive function of sound design in contemporary Uzbek feature cinema through a scientific-theoretical and analytical approach. The research comprehensively analyzes the influence of sound design on dramaturgical structure, character psychology, and the audience’s emotional perception. In particular, the psychological semantic load of diegetic and non-diegetic sounds, background noise, musical timbres, and pauses is revealed. Based on selected examples from contemporary Uzbek films, the study scientifically substantiates the role of sound design as a psychological guiding factor that enhances internal dramatic tension, expresses characters’ inner experiences, and contributes to narrative development.